Data protection of internet of things for edge computing and deep learning and governance of cyberspace. (15th May 2023) - Li, Zhi; Ge, Yuemeng; Jia, Min; Xu, Yanrui
The purpose is to deal with the network security problems in the background of the high information age, ensure the popularisation of Internet of things (IoT) technology based on Internet technology, and protect the information, life and property security of countries and individuals. First, the principle and advantages of edge computing and deep learning technology are described. Then, the current laws of IoT data protection are introduced, and the moral and ethical issues involved in IoT data are discussed. Finally, the research results of cyberspace governance in China and Europe are studied. The results show that the respondents who do not know anything about the data protection regulations and do not focus on the regulations are 27% and 18%, respectively.